2022
DOI: 10.1101/2022.08.20.22279023
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Brain microstructural changes and fatigue after COVID-19

Abstract: Background Fatigue and cognitive complaints are the most frequent persistent symptoms in patients after severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. This study aimed to assess fatigue and neuropsychological performance and investigate changes in the thickness and volume of gray matter (GM) and microstructural abnormalities in the white matter (WM) in a group of patients with mild-to-moderate coronavirus disease 2019 (COVID-19). Methods We studied 56 COVID-19 patients and 37 matched c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…One possible mechanism of cognitive impairment in PCD might be the disruption of connections between brain regions caused by neuroinflammation and demyelination due to COVID-19 [44,[83][84][85][86][87][88][89][90].…”
Section: Possible Physiological Basis Of Covid-19-related Cognitive C...mentioning
confidence: 99%
See 1 more Smart Citation
“…One possible mechanism of cognitive impairment in PCD might be the disruption of connections between brain regions caused by neuroinflammation and demyelination due to COVID-19 [44,[83][84][85][86][87][88][89][90].…”
Section: Possible Physiological Basis Of Covid-19-related Cognitive C...mentioning
confidence: 99%
“…Most researchers believe that neuroinflammation leading to impaired connectivity might be the main cause of cognitive impairment after COVID-19. Several studies have demonstrated neuroinflammation [83,84] as well as disrupted connectivity and demyelination [44,85,86,88] in post-COVID patients. Since microglial and astroglial reactivation lead to impaired oligodendrocyte functioning and renewal [91][92][93], demyelination or decreased remyelination might also play important roles in cognitive changes in PCD patients.…”
Section: Possible Physiological Basis Of Covid-19-related Cognitive C...mentioning
confidence: 99%